E.H.Carr: A Critical Appraisal
XXII, 352 p.
Keywords: E.H. Carr (1892-1982) was born into security but lived a life of controversy. Attacked for appeasing both Hitler and Stalin, he was not only one of the most productive writers of the Twentieth-century but one of its most provocative as well. In this book - the first ever to deal critically but fairly with Carr's contribution to international relations, Soviet Studies and the study of history - sixteen internationally respected authors grapple with his complex intellectual legacy. For those seriously interested in understanding the life and times of this most English of establishment radicals this is the place to begin.